If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16p + -6(3 + -4p) = 4(p + -3) + -22 -16p + (3 * -6 + -4p * -6) = 4(p + -3) + -22 -16p + (-18 + 24p) = 4(p + -3) + -22 Reorder the terms: -18 + -16p + 24p = 4(p + -3) + -22 Combine like terms: -16p + 24p = 8p -18 + 8p = 4(p + -3) + -22 Reorder the terms: -18 + 8p = 4(-3 + p) + -22 -18 + 8p = (-3 * 4 + p * 4) + -22 -18 + 8p = (-12 + 4p) + -22 Reorder the terms: -18 + 8p = -12 + -22 + 4p Combine like terms: -12 + -22 = -34 -18 + 8p = -34 + 4p Solving -18 + 8p = -34 + 4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4p' to each side of the equation. -18 + 8p + -4p = -34 + 4p + -4p Combine like terms: 8p + -4p = 4p -18 + 4p = -34 + 4p + -4p Combine like terms: 4p + -4p = 0 -18 + 4p = -34 + 0 -18 + 4p = -34 Add '18' to each side of the equation. -18 + 18 + 4p = -34 + 18 Combine like terms: -18 + 18 = 0 0 + 4p = -34 + 18 4p = -34 + 18 Combine like terms: -34 + 18 = -16 4p = -16 Divide each side by '4'. p = -4 Simplifying p = -4
| 3x^2=53 | | 13*+30=21*+14 | | (x+6)(x+6)=-7 | | m^3+1=0 | | 3x+7=15-4x | | -2(4x-3)=6 | | 49m^2-126m+81=0 | | 3x+8y=2 | | x^2-2x+3=y | | (x+4)(4-x)=3(3x-2) | | x^2-2x+3= | | 5+4=x-20 | | 1.3x+7.2=-0.7x-2.8 | | 6(3+2x)=-18 | | 2x^2-6=26 | | 4x+3x=99+2x+1 | | 8y^2-2y-3=0 | | 60x^2-30x=0 | | 9x^6+27x^4= | | 2d^2+9d=5 | | 6r^2-11r=35 | | 2.50x+.75=7.75 | | 9=3(5x+2) | | 2+x=5-3x | | -3(t-5)-(t-2)=10 | | 13=3x+3 | | -1.4=0.4x | | 3z^2+z-4=0 | | n^2+6n+27=47 | | (2x-9)=7 | | 2x-3=61x | | n^2+6n+27=0 |